Effects of kappa-opioid receptor stimulation on addiction-related behavior in female rats: differences along the rostro-caudal axis of the nucleus accumbens shell - Annie Hawks; Mary B. Spodnick; Malcolm C. Jennings; Christina M. Nelson; Megan Peng; Gavin Vaughan; Brody A. Carpenter; Chan N. Chung; Anushree N. Karkhanis; Jessica R. Barson (Psychopharmacology, 2026)
Rationale Affective behavioral effects of kappa-opioid receptor (KOR) stimulation have been found to vary between the rostral and caudal nucleus accumbens (NAc) shell, but this has so far only been demonstrated in males. Objectives To examine the effects of KOR activation in subregions of the NAc shell on affective and motivated behavior in females. Methods In one group of Long-Evans rats, females were given access to 20% ethanol in an intermittent-access procedure and then injected within-subject with the selective KOR agonist, U50,488, or vehicle in the rostral or caudal NAc shell, prior to being tested in a light-dark box or having their ethanol drinking monitored. In a second group of Long-Evans rats, females and males were trained to self-administer 10% sucrose and then injected within-subject with U50,488 or vehicle in the rostral or caudal NAc shell, prior to being tested in a progressive ratio (PR) schedule of reinforcement. Results Injection of U50,488 into the caudal but not rostral NAc shell reduced the number of entries into the light chamber of a light-dark box, while injection of U50,488 into the rostral but not caudal NAc shell reduced ethanol drinking. Injection of U50,488 into neither the rostral nor the caudal NAc shell had any effect on any measure of sucrose intake. Conclusions The present findings confirm and extend previous findings regarding the effects of KOR activation in subregions of the NAc shell on affective and motivated behavior. These results support a continued focus on the KOR as a possible pharmacotherapeutic target.

Large Haplotypes Linked to Climate and Life History Variation in Divergent Lineages of Atlantic Salmon ( Salmo salar ) - S. J. Lehnert; T. Kess; P. Bentzen; N. Barson; S. Lien; J. B. Dempson; I. R. Bradbury (Molecular Ecology, 2025)
Advances in sequencing are revealing that linked genomic architectures, enabling the evolution of co‐adapted alleles at multiple loci, often shape complex phenotypes. Several recent studies have identified such architectures (e.g., chromosomal rearrangements and supergenes) contributing to adaptation or divergence across diverse species, from plants to mammals. Specifically, within Atlantic salmon ( Salmo salar ), genomic studies are revealing large haplotypes and structural variants that may underpin local adaptation in the species. Using data from > 4000 individuals from 134 locations spanning the North Atlantic Ocean, we identify a large (~3 Mbp) genomic region on Ssa18 showing patterns of differentiation and linkage disequilibrium (LD) indicative of a large haplotype block containing three divergent haplotypes (herein A, B and C haplotypes). In Europe, haplotypes A and B were common, whereas A and C were more common within North America, suggesting a shared ‘ancestral’ A haplotype, with different continent‐specific alternative haplotypes. Data support independent origins of divergent haplotypes in each continent, as well as signals of trans‐oceanic introgression of haplotypes. Haplotype frequency is strongly associated with latitude, climate and life history (smolt age); however, the strength and direction of these relationships vary across continents. Overall, our analyses were consistent with other studies that identify chromosomal rearrangements; however, long‐read sequence data did not find evidence of a structural variant, and instead an ancestral fusion may explain the formation and maintenance of the observed haplotypes. Our study contributes to ongoing efforts to understand the evolutionary role of linked genomic architecture in Atlantic salmon and its significance in salmonid diversification.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Gyrodactylus pictae n. sp. (Monogenea: Gyrodactylidae) from the Trinidadian swamp guppy Poecilia picta Regan, with a discussion on species of Gyrodactylus von Nordmann, 1832 and their poeciliid hosts - J. Cable; C. van Oosterhout; N. Barson; P. D. Harris (Systematic Parasitology, 2005)